Trajectories of adherence to intravenous biological treatment in patients with inflammatory bowel disease: a longitudinal analysis - Dong, Xiuli; Zhu, Suyan; Jin, Yiyi; Ren, Chaoqun; Chen, Chunyan (Frontiers in Pharmacology, 2024)
Background: Long-term biological therapies for inflammatory bowel disease (IBD) include infliximab and vedolizumab, which are administered intravenously. Although highly effective, non-adherence to these biologics is common and is associated with adverse sequelae and loss of response. Objective: In this study, we aim to characterize long-term intravenous biologic adherence trajectories among IBD patients and identify the factors linked with these trajectories. Methods: We conducted a retrospective multicenter study of IBD patients over two years to assess their adherence to infliximab and vedolizumab. The date of infusion was determined based on medical and pharmacy records. Using group-based trajectory modeling (GBTM), adherence trajectories were identified based on patients' 90-day coverage of days over time. The effect of relevant variables on adherence behavior was assessed using multinomial regression analysis. Results: 374 patients with IBD were included in the study, 68.2% males with a median age of 34.3 (IQR 28.0-44.4) years old. Three distinct adherence trajectories were identified for intravenous biologics: “consistent adherence” (n = 136, 36.4%), “slow decline” (n = 137, 36.6%) and “rapid decline” (n =101, 27.0%). Compared with consistent adherence, concomitant use of aminosalicylates (OR 3.49, 95% CI 1.34–9.05) was associated with a significantly greater risk of rapid decline. Conversely, being married at the initiation of biologics (OR 0.43, 95% CI 0.19–0.95) and having been hospitalized within preceding years (OR 0.44, 95% CI 0.23–0.88) appeared to have a protective effect against rapid decline. Additionally, being male (OR 0.57, 95% CI 0.32–1.01) was found to be protective against slow decline. Conclusion: Distinct adherence patterns for infusion biologics among IBD patients have been identified, offering valuable insights to refine the design and timing of adherence interventions. However, only limited factors were found to be associated with specific adherence trajectories, revealing the complex nature of adherence behavior.